1979
DOI: 10.1111/j.1365-3083.1979.tb03271.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced in Vitro Response of CSF Lymphocytes to Mitogen Stimulation in Multiple Sclerosis

Abstract: By means of a microculture technique and calculation of incorporation of 14C-thymidine, cerebrospinal fluid (CSF) lymphocytes from multiple sclerosis (MS) patients showed low or absent proliferation when stimulated with phytohaemagglutinin, concanavalin A, or pokeweed mitogen, in contrast to peripheral blood lymphocytes (PBL) obtained simultaneously and investigated in parallel. A lower proliferation of CSF lymphocytes compared with PBL was also found in acute aseptic meningitis, although it has been reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
1

Year Published

1984
1984
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 15 publications
1
12
1
Order By: Relevance
“…This disparity may be explained by the different pathways of activation fol lowed by T cells after stimulation with these molecules. The low sHLA secretion by MS PBL on PHA activation could be a consequence of prolonged sensitization to an as yet unidentified antigen [14], The normal cell prolifera tion in our cases, similar to results published previously [7], does not invalidate this hypothesis since these events are independent of each other [9]. Since MS lymphocytes seem to secrete elevated levels of y-interferon [15,16], another explanation for our findings is that this molecule could inhibit sHLA secretion in our patients, an effect that we have previously found in vitro in the normal pop ulation [unpubl.…”
Section: Discussionmentioning
confidence: 99%
“…This disparity may be explained by the different pathways of activation fol lowed by T cells after stimulation with these molecules. The low sHLA secretion by MS PBL on PHA activation could be a consequence of prolonged sensitization to an as yet unidentified antigen [14], The normal cell prolifera tion in our cases, similar to results published previously [7], does not invalidate this hypothesis since these events are independent of each other [9]. Since MS lymphocytes seem to secrete elevated levels of y-interferon [15,16], another explanation for our findings is that this molecule could inhibit sHLA secretion in our patients, an effect that we have previously found in vitro in the normal pop ulation [unpubl.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that CSF mononuclear cells respond poorly to mitogens (Kam-Hansen et al 1979), Similarly, it has been found that synovial fluid cells from patients with rheumatoid arthritis also proliferate poorly to mitogens (Stratton et al 1978). In the case of synovial fluid, stimulation was depressed via the CD3 T-cell receptor (TCR) complex, and this could be reversed by the addition of either IL-1 or IL-2 (Lotz et aL 1986).…”
Section: Activation Pathways Of Csf T Cellsmentioning
confidence: 99%
“…Merrill et al (13) demonstrated loss of natural killer cell activity in MS CSF, which suggests that MS CSF lymphocytes may be different from cells seen in control CSF. Other laboratories have noted the presence of MS spinal fluid lymphocytes that are reactive to myelin basic protein (14), measles antigen (15-), mitogens (16), and alloantigens (17). Thus, there are large numbers of immunocompetent cells in the CSF of MS patients, and these cells may be different than cells seen in the CSF of patients with other neurologic diseases.…”
Section: Introductionmentioning
confidence: 99%